Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, \(\frac{3}{5}+\frac{-4}{15}=\frac{9}{15}-\frac{4}{15}=\frac{5}{15}=\frac{1}{3}\)
b, \(\frac{-1}{3}+\frac{2}{5}+\frac{2}{15}=\frac{-5}{15}+\frac{6}{15}+\frac{2}{15}=\frac{3}{15}=\frac{1}{5}\)
c, \(\frac{-3}{5}+\frac{7}{21}+\frac{-4}{5}+\frac{7}{5}=\frac{-3}{5}+\frac{1}{3}+\frac{-4}{5}+\frac{7}{5}=\left(\frac{-3}{5}+\frac{-4}{5}+\frac{7}{5}\right)+\frac{1}{3}=\frac{1}{3}\)
d, \(\frac{2}{7}+\frac{1}{9}+\frac{3}{7}+\frac{5}{9}+\frac{-5}{6}=\left(\frac{2}{7}+\frac{3}{7}\right)+\left(\frac{1}{9}+\frac{5}{9}\right)+\frac{-5}{6}=\frac{5}{7}+\frac{6}{9}+\frac{-5}{6}=\frac{90}{126}+\frac{84}{126}+\frac{-105}{126}=\frac{69}{126}=\frac{23}{42}\)
e, \(\frac{-5}{7}+\frac{3}{4}+\frac{-1}{5}+\frac{-2}{7}+\frac{1}{4}=\left(\frac{-5}{7}+\frac{-2}{7}\right)+\left(\frac{3}{4}+\frac{1}{4}\right)+\frac{-1}{5}=\left(-1\right)+1+\frac{-1}{5}=\frac{-1}{5}\)
f, \(\frac{-3}{31}+\frac{-6}{17}+\frac{1}{25}+\frac{-28}{31}+\frac{-1}{17}+\frac{-1}{5}=\left(\frac{-3}{31}+\frac{-28}{31}\right)+\left(\frac{-6}{17}+\frac{-1}{17}\right)+\left(\frac{1}{25}+\frac{-1}{5}\right)=\left(-1\right)+\frac{-7}{17}+\frac{-4}{25}=\frac{-425}{425}+\frac{-175}{425}+\frac{-68}{425}=\frac{-668}{425}\)
Chúc bn học tốt
\(a.\frac{2}{3}+\frac{1}{5}\cdot\frac{10}{7}\)
\(=\frac{2}{3}+\frac{1\cdot2}{1\cdot7}\)
\(=\frac{2}{3}+\frac{2}{7}=\frac{2\cdot7}{21}+\frac{2\cdot3}{21}=\frac{14}{21}+\frac{6}{21}=\frac{20}{21}\)
\(b.\frac{2}{7}\cdot\frac{4}{7}+\frac{2}{7}\cdot\frac{3}{7}\)
\(=\frac{2}{7}\cdot\left(\frac{4}{7}+\frac{3}{7}\right)\)
\(=\frac{2}{7}\cdot\frac{7}{7}=\frac{2}{7}\cdot1=\frac{2}{7}\)
\(c.\left[-\frac{1}{4}+\frac{3}{10}\right]:\left(-\frac{3}{5}\right)-\frac{7}{6}\)
\(=\left[-\frac{5}{20}+\frac{6}{20}\right]:\left(-\frac{3}{5}\right)-\frac{7}{6}\)
\(=\frac{1}{20}:\left(-\frac{3}{5}\right)-\frac{7}{6}\)
\(=\frac{1}{20}\cdot\left(-\frac{5}{3}\right)-\frac{7}{6}\)
\(=\frac{1\cdot\left(-1\right)}{4\cdot3}-\frac{7}{6}\)
\(=\left(-\frac{1}{12}\right)-\frac{7}{6}=\left(-\frac{1}{12}\right)-\frac{14}{12}=-\frac{15}{12}\)
bài 2 :a) \(2x-2\frac{2}{7}=2\frac{5}{7}\)
\(2x=2\frac{5}{7}-2\frac{2}{7}\)
\(2x=\left(2-2\right)+\left(\frac{5}{7}-\frac{2}{7}\right)\)
\(2x=0+\frac{3}{7}\)
\(2x=\frac{3}{7}\)
\(x=\frac{3}{7}:2=\frac{3}{7}\cdot\frac{1}{2}=\frac{3}{14}\)
\(b.\frac{17}{13x}=\frac{4}{39}\)
\(\Rightarrow13x\cdot4=17\cdot39\)
\(\Rightarrow13x\cdot4=663\)
\(\Rightarrow13x=663:4\)
\(\Rightarrow13x=165,75\)
\(\Rightarrow x=165,75:13\)
\(\Rightarrow x=12,75\)
\(****nha!!!!!!!!!!!!\)
a: \(=\dfrac{5}{\dfrac{2}{5}}\cdot\dfrac{4}{\dfrac{2}{7}}+\dfrac{5}{\dfrac{5}{7}}\cdot\dfrac{5}{\dfrac{2}{5}}\)
\(=5\cdot\dfrac{5}{2}\cdot4\cdot\dfrac{7}{2}+5\cdot\dfrac{5}{2}\cdot5\cdot\dfrac{7}{5}\)
\(=\dfrac{25}{2}\left(14+7\right)=\dfrac{25}{2}\cdot21=\dfrac{525}{2}\)
b: \(=\dfrac{3}{4}-2+\dfrac{1}{2}\cdot\dfrac{12}{5}-\dfrac{1}{4}\)
\(=\dfrac{6}{5}-2+\dfrac{1}{2}=-\dfrac{3}{10}\)
3/7 *14/5 - 1/2 = 6/5-1/2 = 7/10
2/5 - 3/5 *5/10 = 2/5 - 3/10 = 1/10
4/13 *5/11 + 4/13 *6/11 - 4/13
= 4/13*5/11 +4/13 *6/11 - 4/13 *1
= 4/13 *(5/11+ 6/11 - 1)
= 4/13 *0
=0
\(\dfrac{2}{5}+\dfrac{-7}{4}\)
\(=\dfrac{2\cdot4}{5\cdot4}+\dfrac{-7\cdot5}{4\cdot5}\)
\(=\dfrac{8}{20}+\dfrac{-35}{20}\)
\(=\dfrac{8+\left(-25\right)}{20}\)
\(=\dfrac{-17}{20}\)
-27 phần 20 mà